SUBJEKTIVITAS KOLEKTIF : KRISIS EKSISTENSI DALAM KARYA SENI - Iksan, Nur (Studi Budaya Nusantara, 2019)
Abstract As dynamic humans beings who are obliged to always improve the quality of their life, they should not adjust and neutralize about their value for the outside offer. Ideally, human must engaged in every process and be the subject for it if they want to be a true self. A process that undertake to get a holistic knowledge as a perfection foundation for the meaning of their life. Being themself and be men that freely and be aware of all their actions. A consequence must faced with put the choice based on the autonomous authority, for a faith and appreciation in the activity. However, in the global mode for this time, we will very difficult to find the human of life that are able to reach into authenticity in themself. In the reality, through the mass media the authoritarian rule legal and illegal have created mass culture in a view. This phenomenon can be seen in the work of the mass media that presents the imagination that artificial continuously with mechanisms of hypnosis as injection technique awareness. A uniformity system that offers “ established ” with basic systems of material, imaging, social status and even morality. The offering above without based of knowledge about subjectively will increasingly the encourage individuals in experiencing an identity crisis, aware for media massa presenting and the end it’s make a majority view of society. The phenomenon described above as an idea of the creation printmaking art works with an autocriticism charge of the human condition is experiencing an existential crisis, by using the method of creation: exploration, brainstorming, and shaping or embodiment.the process of assembling the excess of graphic work through reproduction into the canvas medium with puzzele techniques. Art work of the collective subjectivity theme is expected to be a reflective media of humans in an existential crisis.